2016
DOI: 10.1016/j.jeurceramsoc.2015.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element modeling of the electro-thermal contacts in the spark plasma sintering process

Abstract: Spark plasma sintering (SPS) is a breakthrough process for powder consolidation assisted by pulsed current and uniaxial pressure. In order to model the temperature variations of the tools during a SPS cycle, the Graphite-Papyex-Graphite contact phenomena are studied experimentally and modeled by finite element calculations. Compared to conducting materials, the thermo graphic image of an insulating sample (alumina) shows strongly localized heating along the Papyex implying contact effects are predominant. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 16 publications
2
48
0
Order By: Relevance
“…Indeed, the electrical current should get round the alumina sample by crossing the two interfaces punch/die. In a previous paper [15], we show the current density is locally very high in the area near the punch outlet and induces at this place a strong heat generation by Joule effect. We also showed that a non-negligible quantity of this heat is maintained in the papyex thickness because of the presence of high TCR papyex/punch and TCR papyex/die and this heat can diffuse along the papyex to the sample.…”
Section: Spacer/punch Punch/sample Sample/die and Punch/die Calibramentioning
confidence: 59%
See 4 more Smart Citations
“…Indeed, the electrical current should get round the alumina sample by crossing the two interfaces punch/die. In a previous paper [15], we show the current density is locally very high in the area near the punch outlet and induces at this place a strong heat generation by Joule effect. We also showed that a non-negligible quantity of this heat is maintained in the papyex thickness because of the presence of high TCR papyex/punch and TCR papyex/die and this heat can diffuse along the papyex to the sample.…”
Section: Spacer/punch Punch/sample Sample/die and Punch/die Calibramentioning
confidence: 59%
“…We used, in this study, the calibration methodology employed in our two previous papers [15,16]. This methodology is a trial-and-error approach involving minimization of the experimental/simulated temperature field by the ECR and TCR calibration.…”
Section: The Calibration Methodsologymentioning
confidence: 99%
See 3 more Smart Citations